Study of the Vibratory Behavior of the Bridge under the Passage of Mobile Loads Convoys: Comparative Study between Uni-dimensional and Three-dimensional Modeling - Meriem Ouchenane (Civil Engineering Journal, 2018)
In order to understand the dynamic behavior of bridges under the passage of convoys of moving vehicles, it was necessary to start with the example of a single moving force, however, this study was deemed insufficient because the bridge is under several vehicle forces simultaneously. As a result, this study focuses on the vibration of bridges subjected to convoys of several mobile loads. Based on the analysis of the equation of motion that manage this behavior for the case of a simply-supported unamortized thin beam, subjected to convoys of one, two, and three forces at constant speed. In order to verify the solution obtained for a convoy of n forces through the superposition of solutions of single force with a time offset, see the influence of the spacing ‘e’ between the forces of the convoy on the dynamic amplification factor and compare the results of the analytical study with those derived from the real model established by the software Csi Bridge.